A new monoclonal antibody, mAb 204-11, that influences the binding of platelet GPVI to fibrous collagen - Moroi, Masaaki; Mizuguchi, Jun; Kawashima, Sachiko; Nagamatsu, Michiko; Miura, Yoshiki; Nakagaki, Tomohiro; Ito, Katsuaki; Jung, Stephanie M. (Thrombosis and Haemostasis, 2003)
The newly identified platelet collagen receptor glycoprotein VI binds to fibrous collagen, inducing platelet activation. Several antibodies against GPVI have been reported, including a patient’s auto-antibodies, that activates platelets through their ability to crosslink this glycoprotein. We have developed a monoclonal antibody (mAb) against GPVI using the recombinant extracellular domain of GPVI as an antigen. This antibody, mAb 204-11, induced platelet aggregation and tyrosine phosphorylation of proteins similar to those induced by GPVI-reactive proteins, collagen and convulxin. Its interaction with GPVI was analyzed by measuring the effect of the antibody on GPVI binding to collagen using a dimeric form of recombinant GPVI, GPVI-Fc2. MAb 204-11 inhibited the binding of GPVI-Fc2 to fibrous collagen particles, but enhanced the GPVI binding to immobilized collagen, suggesting that the antibody binds to a region near the collagen binding site of GPVI. MAb 204-11 also inhibited the GPVI binding to convulxin at a low concentration, but not completely. Since mAb 204-11 reacts specifically with GPVI and is applicable for immunoblotting and immunoprecipitation, this antibody would be useful for studies on GPVI.
Keywords: Platelet; GPVI; monoclonal antibody; collagen receptor; collagen